BERGEMBIRA dengan sains / Hans Jurgen Press; penerjemah, R.S. Hardjapamekas, Diplom Sprachlehrer, Djadjang Madya Patriana; penyunting, Dadi Pakar, Nova Yulianawati, Yuza Terzalgi - Hardjapamekas, R.S; Diplom Sprachlehrer; Djadjang Madya Patriana; Dadi Pakar; Nova Yulianawati; Yuza Terzalgi; Hans Jurgen Press (Angkasa, 2013)
x, 270 hlm. : ilus. ; 25 cm.